Representing theories of change: technical challenges with evaluation consequences - and Davies, Rick (Journal of Development Effectiveness, 2018)
This paper looks at the technical issues associated with the representation of Theories of Change and the implications of design choices for the evaluability of those theories. The focus is on the description of connections between events rather than the events themselves, because this is seen as a widespread design weakness. Using examples and evidence from Internet sources six structural problems are described along with their consequences for evaluation. The paper then outlines a range of different ways of addressing these problems that could be used by programme designers, implementers and evaluators. The paper concludes with some caution speculating on why the design problems are so endemic but also pointing a way forward. Four strands of work are identified that CEDIL and DFID could invest in to develop solutions identified in the paper.
Keywords: Evaluation; evaluability; representation; theory of change